Diverse and durophagous: Early Carboniferous chondrichthyans from the Scottish Borders. (March 2017) - Richards, Kelly R.; Sherwin, Janet E.; Smithson, Timothy R.; Bennion, Rebecca F.; Davies, Sarah J.; Marshall, John E. A.; Clack, Jennifer A.
ABSTRACT: Chondrichthyan teeth from a new locality in the Scottish Borders supply additional evidence of Early Carboniferous chondrichthyans in the UK. The interbedded dolostones and siltstones of the Ballagan Formation exposed along Whitrope Burn are interpreted as representing a restricted lagoonal environment that received significant amounts of land-derived sediment. This site is palynologically dated to the latest Tournaisian–early Viséan. The diverse dental fauna documented here is dominated by large crushing holocephalan toothplates, with very few, small non-crushing chondrichthyan teeth. Two new taxa are named and described. Our samples are consistent with worldwide evidence that chondrichthyan crushing faunas are common following the Hangenberg extinction event. The lagoonal habitat represented by Whitrope Burn may represent a temporary refugium that was host to a near-relict fauna dominated by large holocephalan chondrichthyans with crushing dentitions. Many of these had already become scarce in other localities by the Viséan and become extinct later in the Carboniferous. This fauna provides evidence of early endemism or niche separation within European chondrichthyan faunas at this time. This evidence points to a complex picture in which the diversity of durophagous chondrichthyans is controlled by narrow spatial shifts in niche availability over time.